Chip-to-Chip and On-Chip Communications - Nossek, Josef A.; Russer, Peter; Noll, Tobias; Mezghani, Amine; Ivrlač, Michel T.; Korb, Matthias; Mukhtar, Farooq; Yordanov, Hristomir; Russer, Johannes A. (IntechOpen, 2013)
None